Magnetically responsive microbubbles as delivery vehicles for targeted sonodynamic and antimetabolite therapy of pancreatic cancer - Sheng, Y; Beguin, E; Nesbitt, H; Kamila, S; Owen, J; Barnsley, L; Callan, B; O'Kane, C; Nomikou, N; Hamoudi, R; Taylor, M; Love, M; et al. (Elsevier, 2017)
Magnetically responsive microbubbles (MagMBs), consisting of an oxygen gas core and a phospholipid coating functionalised with Rose Bengal (RB) and/or 5-fluorouracil (5-FU), were assessed as a delivery vehicle for the targeted treatment of pancreatic cancer using combined antimetabolite and sonodynamic therapy (SDT). MagMBs delivering the combined 5-FU/SDT treatment produced a reduction in cell viability of over 50% when tested against a panel of four pancreatic cancer cell lines in vitro. Intravenous administration of the MagMBs to mice bearing orthotopic human xenograft BxPC-3 tumours yielded a 48.3% reduction in tumour volume relative to an untreated control group (p<0.05) when the tumour was exposed to both external magnetic and ultrasound fields during administration of the MagMBs. In contrast, application of an external ultrasound field alone resulted in a 27% reduction in tumour volume. In addition, activated caspase and BAX protein levels were both observed to be significantly elevated in tumours harvested from animals treated with the MagMBs in the presence of magnetic and ultrasonic fields when compared to expression of those proteins in tumours from either the control or ultrasound field only groups (p<0.05). These results suggest MagMBs have considerable potential as a platform to enable the targeted delivery of combined sonodynamic/antimetabolite therapy in pancreatic cancer.